The role of social assistance in African crises: A systematic literature review - Hirvonen, Kalle; Justino, Patricia; Oliveira, Rodrigo (United Nations University, 2024)
This systematic review examines the effectiveness of social assistance programmes in protecting households in Africa—a region highly vulnerable to climate change, conflict, and other shocks—during periods of crisis. Despite the significant increase in the number of these programmes over the past two decades, the need for emergency aid remains. Our review focuses on quantitative studies using microdata to assess the impact of these programmes on household income, poverty, assets, and food security outcomes during crises. We find that large, predictable, and consistent transfers are effective in protecting households and building resilience, as they enable households to accumulate buffer stocks and better plan for future shocks. However, challenges with timely implementation often hinder their effectiveness. Cash-plus programmes, which integrate consumption support with livelihood interventions, show particular promise in fostering long-term resilience, though the evidence base remains too limited to draw broader conclusions.